Enhancement of photoacoustic detection of inhomogeneities in polymers - Grondona, P. (2013)
We report a series of experiments on laser pulsed photoacoustic excitationin turbid polymer samples addressed to evaluate the sound speed in the samples and the presence of inhomogeneities in the bulk. We describe a system which allows the direct measurement of the speed of the detected waves by engraving the surface of the piece under study with a fiduciary pattern of black lines..We also describe how this pattern helps to enhance the sensitivity for the detection of an inhomogeneity in the bulk. These two facts are useful for studies in soft matter systems including, perhaps, biological samples. We have performed an experimental analysis on Grilon® samples in different situations and we show the limitations of the method.